2014
DOI: 10.1088/0029-5515/55/1/013015
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of multiple flux tubes in sawtoothing KSTAR plasmas heated by electron cyclotron waves: I. Experimental analysis of the tube structure

Abstract: Multiple (two or more) flux tubes are commonly observed inside and/or near the q = 1 flux surface in KSTAR tokamak plasmas with localized electron cyclotron resonance heating and current drive (ECH/CD). Detailed 2D and quasi-3D images of the flux tubes obtained by an advanced imaging diagnostic system showed that the flux tubes are m/n = 1/1 field-aligned structures co-rotating around the magnetic axis. The flux tubes typically merge together and become like the internal kink mode of the usual sawtooth, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…In recent experiments on KSTAR (Korea Superconducting Tokamak Advanced Research) with electron cyclotron heating (ECH), multiple hot spots were observed in two-dimensional electron cyclotron emission (ECE) images of the plasma core during the ramp phase of internal disruptions ('sawteeth') [1]. These structures appear inside the sawtooth inversion radius and have helicity h = m/n = 1 [2], where m and n are the poloidal and toroidal mode numbers. They have lifetimes of up to several milliseconds and were robustly observed in several experimental campaigns with different plasma and drive parameters as summarized in table 1.…”
Section: Background and Experimental Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…In recent experiments on KSTAR (Korea Superconducting Tokamak Advanced Research) with electron cyclotron heating (ECH), multiple hot spots were observed in two-dimensional electron cyclotron emission (ECE) images of the plasma core during the ramp phase of internal disruptions ('sawteeth') [1]. These structures appear inside the sawtooth inversion radius and have helicity h = m/n = 1 [2], where m and n are the poloidal and toroidal mode numbers. They have lifetimes of up to several milliseconds and were robustly observed in several experimental campaigns with different plasma and drive parameters as summarized in table 1.…”
Section: Background and Experimental Evidencementioning
confidence: 99%
“…Figure 1 shows a schematic overview of how the systematic variation of the vertical deposition location Y dep of ECH in discharge 9214 leads to different flux tube patterns. The background and details of these experiments are presented in a companion paper [2]. The purpose of the present paper is to discuss the experimental results from a theoretical point of view and Table 1.…”
Section: Background and Experimental Evidencementioning
confidence: 99%
“…This has been well demonstrated in beautiful KSTAR experiments ( Figure 13) [25]. In these experiments, the fine Te (and so, the current density) structure was registered from the image of the second EC harmonic emission.…”
Section: Internal Transport Barriers (Itbs)mentioning
confidence: 52%
“…Energy overload of the islands cannot reduce m below the minimum value for a given surface (m = 1 in the KSTAR case shown in Figure 13). Further energy growth should lead to internal disruption, which is the mechanism that expels the energy through the barrier (see Figures 11 and 12 as well as the KSTAR paper [25]). In this case, after the disruption, Γ(r) decreases in the region with q ≤ 1, and m/n changes from 1/1 to 8/8.…”
Section: Internal Transport Barriers (Itbs)mentioning
confidence: 99%
“…However, there is a gap between experimental study and numerical simulation, since few experiments have been carried out to investigate the 3Drelated issues, except the quasi-3D imaging of the edge-localized mode studied on KSTAR [17]. Although quasi-3D images of multiple flux tubes were studied in the core plasma region [18,19] on KSATR, they are actually reconstructed by two partial pieces of = q 1 surface measured by two ECEI systems with a toroidal separation. The entire = q 1 surface cannot be covered by a single set of the ECEI system due to the limited intermediate frequency (IF) bandwidth of the systems.…”
Section: Introductionmentioning
confidence: 99%